1) "x^2y''+xy'-y=x^2e^x"
We will replace
"x=e^t, t=ln|x|\\\\\ny'=\\frac{dy}{dx}=\\frac{y'_t}{x'_t}=\\frac{y'_t}{e^t}=e^{-t}y'_t\\\\\ny''=\\frac{dy'}{dx}=\\frac{(e^{-t}\\cdot y'_{t})'}{e^t}=\\frac{y''_{t}e^{-t}-e^{-t}y'_t}{e^t}=e^{-2t}(y''_t-y'_t)"
then
"e^{2t}e^{-2t}(y''-y')+e^te^{-t}y'-y=e^{2t}\\cdot e^{e^t}\\\\\ny''-y'+y'-y=e^{2t}\\cdot e^{e^t}\\\\\ny''-y=e^{2t}\\cdot e^{e^t}"
a)
"y''-y=0\\\\\n\\lambda^2-1=0\\\\\n\\lambda_1=1, \\lambda_2=-1\\\\\ny_1=e^t, y_2=e^{-t}\\\\\ny_0=c_1e^t+c_2e^{-t}"
b)
"y=c_1(t)e^t+c_2(t)e^{-t}\\\\"
"\\left\\{\\begin{matrix}\n c'_1e^t+c'_2e^{-t}=0 \\\\\n c'_1e^t-c'_2e^{-t}=e^{2t}e^{e^t}\n\\end{matrix}\\right.\\\\\n2c'_1e^t=e^{2t}e^{e^t}\\\\\nc'_1=\\frac{1}{2}e^{t}e^{e^t}\\\\\nc_1=\\frac{1}{2}\\int e^{t}e^{e^t}dt=\\frac{1}{2}\\int e^{e^t}d(e^t)=\\\\\n=\\frac{1}{2}e^{e^t}+k_1"
"2c'_2e^{-t}=-e^{2t}e^{e^t}\\\\\nc'_2=-\\frac{1}{2}e^{3t}e^{e^t}\\\\\nc_2=-\\frac{1}{2}\\int e^{3t}e^{e^t}dt=-\\frac{1}{2}\\int e^{2t}e^{e^t}d(e^t)"
let "u=e^t" then
"\\int e^{2t}e^{e^t}de^t=\\int u^2e^udu=u^2e^u-\\int2ue^udu=\\\\\n=u^2e^u-2(ue^u-\\int e^udu)=u^2e^u-2ue^u+2e^u\\\\\nc_2=-\\frac{1}{2}(u^2e^u-2ue^u+2e^u)+k_2=\\\\\n=-\\frac{1}{2}(e^{2t}e^{e^t}-2e^te^{e^t}+2e^{e^t})+k_2"
Then
"y(t)=(\\frac{1}{2}e^{e^t}+k_1)e^t+\\\\\n+(-\\frac{1}{2}(e^{2t}e^{e^t}-2e^te^{e^t}+2e^{e^t})+k_2)e^{-t}\\\\\ny(x)=(\\frac{1}{2}e^x+k_1)x+\\\\\n+(-\\frac{1}{2}(x^2e^x-2xe^x+2e^x)+k_2)\\frac{1}{x}\\\\"
2)
"y''+a^2y=cosecax=\\frac{1}{sinax}"
a)
"y''+a^2y=0\\\\\n\\lambda^2+a^2=0\\\\\n\\lambda_1=ai, \\lambda_2=-ai\\\\\ny_1=cosax, y_2=sinax\\\\\ny_0=c_1cosax+c_2sinax"
b)
"y=c_{1}(x)cosax+c_2(x)sinax\\\\\n\\left\\{\\begin{matrix}\n c'_1cosax+c'_2 sinax=0 \\\\\n -a c'_1sinax+ac'_2 cosax=\\frac{1}{sinax} \n\\end{matrix}\\right."
"\\Delta=\\begin{vmatrix}\n cos ax & sinax\\\\\n -asinax & acosax\n\\end{vmatrix}=a\\\\\n\\Delta_1=\\begin{vmatrix}\n 0 & sinax\\\\\n \\frac{1}{sinax} & acosax\n\\end{vmatrix}=-1\\\\\n\\Delta_2=\\begin{vmatrix}\n cos ax & 0\\\\\n -asinax & \\frac{1}{sinax}\n\\end{vmatrix}=\\frac{cosax}{sinax}\\\\\nc'_{1}=\\frac{\\Delta_1}{\\Delta}=\\frac{-1}{a}\\\\\nc_{1}=\\int\\frac{-1}{a}dx=-\\frac{x}{a}+k_1\\\\\nc'_2=\\frac{\\Delta_2}{\\Delta}=\\frac{1}{a}\\cdot\\frac{cosax}{sinax}\\\\\nc_2=\\int\\frac{1}{a}\\cdot\\frac{cosax}{sinax}dx=\\frac{1}{a^2}ln|sinax|+k_2"
"y=(-\\frac{x}{a}+k_1)cosax+(\\frac{1}{a^2}ln|sinax|+k_2)sinax"
3) "y''-\\cot x y'- \\sin^2x y=\\cos x-\\cos^3x"
We will replace
"\\cos x=t, x=\\arccos t, \\sin x =\\sqrt{1-t^2}\\\\\ny'=\\frac{dy}{dx}=\\frac{y'_t}{x'_t}=\\frac{y'_t}{-\\frac{1}{\\sqrt{1-t^2}}}=-\\sqrt{1-t^2} y'_t\\\\\ny''=\\frac{dy'}{dx}=\\frac{-y''_t\\sqrt{1-t^2}-y'_t\\frac{1}{2\\sqrt{1-t^2}}(-2t)}{-\\frac{1}{\\sqrt{1-t^2}}}=\\\\\n=y''_t(1-t^2)-2ty'_t"
input in equation
"y''(1-t^2)-ty'-\\frac{t}{\\sqrt{1-t^2}}(-\\sqrt{1-t^2})y'-\\\\\n-(1-t^2)y=t-t^3\\\\\ny''(1-t^2)-(1-t^2)y=t(1-t^2)\\\\\ny''-y=t,\\\\\ny=y_0+y_1\\\\\na) y''-y=0\\\\\n\\lambda^2-1=0, \\lambda_1=1, \\lambda_2=-1\\\\\ny_1=e^t, y_2=e^{-t}\\\\\ny_0=c_1e^t+c_2e^{-t}\\\\\nb) y_1=at+b"
input in equation
"-at-b=t\\implies a=-1, b=0,\\\\\ny_1=-t\\\\\ny=c_1e^t+c_2e^{-t}-t\\\\\ny=c_1e^{\\cos x}+c_2e^{-\\cos x}-\\cos x"
Comments
Leave a comment